Impact of exposure to extreme heat events during pregnancy on the incidence of congenital heart disease in offspring: a meta-analysis - Manu Raj; Raman Krishna Kumar; Poornima Prabhakaran; Hisham Ahamed; Georg Gutjahr; Perraju Bendapudi; Aparna Hari; Malavika Krishnakumar (BMJ Paediatrics Open)
Background The aetiology of congenital heart disease (CHD) is multifactorial. Environmental risk factors have emerged as an important modifiable determinant of several congenital cardiac conditions. Previous studies have shown a strong relationship between CHD and air pollution. Much less is known about the influence of ambient temperature on CHD. The primary objective of this meta-analysis was to examine the association between exposure to extreme heat events (EHE) during pregnancy and CHD in the offspring.Methods comprehensive literature search was conducted using electronic databases such as Scopus and PubMed, along with a review of secondary references. This process yielded eight studies that met the inclusion criteria: four from the USA, two from China, one from Israel and one from Canada. The risk of bias was assessed using the Newcastle Ottawa scale. Mixed-effect regression was used to pool the estimates of individual studies. Heterogeneity was measured by I2. Results were visualised by a forest plot, a Baujat plot and an albatross plot. Subgroup analyses were performed for climate zones, exposure definitions and the study region. As a sensitivity analysis, a leave-one-out meta-analysis was performed to assess the robustness of the estimates.Results Exposure to EHE during pregnancy increased the risk for CHD in the offspring (OR=1.12, 95% CI 1.04 to 1.34). Studies from the USA observed the smallest effect (OR=1.01, 95% CI 0.91 to 1.13), studies in the continental climate zone observed a slightly larger effect (OR=1.07, 95% CI 0.97 to 1.19), and studies from the temperate climate zone observed the largest effect (OR=1.35, 95% CI 1.23 to 1.48). Subgroup analysis was conducted with respect to exposure, effect definition and region. The residual heterogeneity measures were 88% (exposure), 61% (effect definition) and 38% (Region).Conclusion The association between prenatal EHE exposure and future risk of CHD has important implications for pregnant mothers, infant health and health policy. Future studies should explore the additional burden of CHD contributed by current trends in global ambient temperature in other parts of the world.PROSPERO registration number CRD42023455934